Scapular asymmetry in participants with and without shoulder impingement syndrome; a three-dimensional motion analysis. (November 2016) - Turgut, Elif; Duzgun, Irem; Baltaci, Gul
Abstract: Background: This study analyzed the dynamic three-dimensional scapular kinematics and scapular asymmetry in participants with and without shoulder impingement syndrome. Methods: Twenty-nine participants with shoulder impingement syndrome, have been suffering from unilateral shoulder pain at the dominant arm lasting more than six weeks and thirty-seven healthy controls participated in the study. Scapular kinematics was measured with an electromagnetic tracking device during shoulder elevation in the sagittal plane. Data for bilateral scapular orientation were analyzed at 30°, 60°, 90°, and 120° of humerothoracic elevation and lowering. The symmetry angle was calculated to quantify scapular asymmetry throughout shoulder elevation. Findings: Statistical comparisons indicated that the scapula was more downwardly rotated ( p  < 0.001) and anteriorly tilted ( p  = 0.005) in participants with shoulder impingement syndrome compared to healthy controls. Side-to-side comparisons revealed that the scapula was more anteriorly tilted on the involved side of participants with shoulder impingement syndrome ( p  = 0.01), and the scapula was rotated more internally ( p  = 0.02) and downwardly ( p  = 0.01) on the dominant side of healthy controls. Although there were side-to-side differences in both groups, symmetry angle calculation revealed that the scapular movement was more asymmetrical for scapular internal and upward rotation in individuals with shoulder impingement syndrome when compared with healthy controls ( p  < 0.05). Interpretation: The findings of the study increase our knowledge and understanding of scapular alterations in symptomatic and asymptomatic populations, which creates biomechanical considerations for shoulder assessment and rehabilitation. Highlights: The dynamic scapular kinematics and scapular asymmetry were evaluated. A novel approach was used to quantify scapular asymmetry. Kinematic differences were observed between healthy controls and participants with impingement. The scapular movement was more asymmetrical in participants with impingement.